Study of Parallel implementation of Computational codes - Tyagi, Shekhar (Trinity College Dublin. School of Engineering. Mechanical & Manufacturing Engineering, 2008)
The use of computers to solve scientific problems is abundant and almost a need of the day. As the complexity of the problems increased, the need to get fast and accurate results has also taken an altogether different meaning. The area where one needs to use all the resources at disposal to compute the results efficiently and quickly is known as HPC (High Performance Computing). Evolution of computers has given the idea of using the entire RAM at disposal while computing the results; hence, parallelization becomes highly desirable. The goal of this project is to parallelize distributed memory systems using WINDOWS platform, analyzing some small(computationally) parallelized problems and if possible then trying to implement them for the software ABAQUS(FEM tool). Moreover the parallel program developed can be used for numerical solution to Helmholtz equation. The basic equation governing acoustics is the Helmholtz equation; analytical complications have driven researchers to develop Numerical methods to solve this equation. Numerical methods in turn have posed computational difficulties even with the use of modern day computers, parallelization of solution of Helmholtz equation is the result of these problems. The standard algorithms are available for the Numerical methods and they only need to be programmed on a platform which can support parallel programming. By the implementation of suitable parallel techniques a considerable amount of efficiency with respect to time in obtaining the solutions can be achieved.
Keywords: Parallelisation; MPI; MPICH